CMOS millimeter-wave transmitter design - Lin, Jiafu (2016)
As wireless communication is rapidly becoming an indispensable part of our life, the demand for low cost, highly integrated high data rate communication is increasing. CMOS technology appears to be the most promising option for low cost large volume production. However, CMOS integrated circuit has several obstacles to achieve mass market adoption at the millimeter-wave frequency in terms of output power, efficiency and linearity etc. To tackle these challenges, a multi-dimensional solution involving several blocks has been proposed, which forms the basis of this thesis. We start by explaining the implementation of CMOS on-chip transformer and analysis of its application in the impedance matching network. A three-stage transformer-coupled power amplifier has been proposed with 16.4 dB small signal gain and a 3-dB bandwidth from 54.4 GHz to 66.3 GHz under 1.2 V supply voltage. The three-stage power amplifier exhibits a maximum output power of 11.8 dBm and a PAE of 11.2% in a compact size. To further improve the efficiency, ILPA (Injection Locking Power Amplifier) is investigated. A dual-mode ILPA with a wide injection locking bandwidth has been proposed. The dual-mode ILPA has a wide injection locking range from 50 GHz to 59 GHz, with a maximum gain of 36.5 dB at 54 GHz for the injection locking mode. In addition, a small signal gain of 14 dB and output 1-dB compression point of 9 dBm have been achieved in the linear mode. Finally, in order to achieve high efficiency transmission at the millimeter-wave frequency, an injection-locked transmitter has been studied. Moreover, a low power source-driven double balanced up-conversion mixer with an output 1-dB compression point of -11 dBm, conversion gain of -10 dB and LO leakage better than -43.1 dBc has been demonstrated. The demonstrated ILTX has achieved an output power of 11.48 dBm with an efficiency of 13.6 %. The transmitter has been tested with BPSK signal up to 1 GHz, with a LO power level of -6 dBm. The proposed ILTX can be employed in efficiency sensitive 60 GHz handheld applications. On-chip compact power combiner with high isolation of 28.3 dB at 40 GHz has also been demonstrated for further development of transmitter. All those proposed ideas and demonstrations can be employed in efficient CMOS millimeter circuit design. The measurement results have shown that cost economical and performance acceptable millimeter-wave CMOS solution is feasible.